Measurement of Platelet Microparticles during Cardiopulmonary Bypass by Means of Captured ELISA for GPIIb/IIIa - Miyamoto, Shinji; Marcinkiewicz, Cezary; Edmunds, L. Henry; Niewiarowski, Stefan (Thrombosis and Haemostasis, 1998)
A captured enzyme-linked immunosorbent assay (ELISA) using the disintegrin, kistrin, is described and used to measure platelet microparticles (PMP) generated during open heart surgery. This ELISA detects 75 ng/ml of glycoprotein IIb/IIIa (GPIIa/IIIa) in solution and is more sensitive and less variable than flow cytometry and radioimmunoassay. By ELISA, mean values of GPIIb/IIIa in PMP are 14.2 ± 7.9 μg/ml for outdated platelets and 0.28 ± 0.1 μg/ml in fresh blood from healthy donors. Normal washed platelets (108) contain 8.8 μg of GPIIb/IIIa.In 12 cardiac surgical patients, PMP measured by ELISA significantly increased (p = 0.039) to 0.58 ± 0.3 μg/ml at the end of cardio-pulmonary bypass, but the increase measured by flow cytometry (1207 to 1447 events in PMP gate) was not significant. Neither heparin nor protamine alter PMP. After cardiopulmonary bypass, PMP concentrations return to baseline values before protamine is given. Concentrations of PMP in pericardial blood are greater than in simultaneous perfusate. This ELISA is more sensitive and accurate than alternate methods for measuring PMP and shows the PMP production and rapid clearance during open cardiac surgery.Present address: Dr. Shinji Miyamoto, Department of Cardiovascular Surgery, Oita Medical University, 1-1 Idaigaoka, Oita, Japan